Communication & competition - Jacob K. Goeree; Jingjing Zhang (University of Zurich, Department of Economics, 2012)
Charness and Dufwenberg (American Economic Review, June 2011, 1211-1237) have recently demonstrated that cheap-talk communication raises efficiency in bilateral contracting situations with adverse selection. We replicate their finding and check its robustness by introducing competition between agents. We find that communication and competition act as substitutes: communication raises efficiency in the absence of competition but lowers efficiency with competition, and competition raises efficiency without communication but lowers efficiency with communication. We briefly review some behavioral theories that have been proposed in this context and show that each can explain some but not all features of the observed data patterns. Our findings highlight the fragility of cheap-talk communication and may serve as a guide to refine existing behavioral theories.
Keywords: C92; 330; cheap talk; adverse selection; competition; guilt aversion; lie aversion; inequality aversion; reciprocity; Asymmetrische Information; Kommunikation; Adverse Selektion; Prinzipal-Agent-Theorie; Verhaltensökonomik; Spieltheorie; Theorie